Purchasing power parity in Asian economies: further evidence from rank tests for cointegration - Liew, Venus Khim-Sen; Lee, Hock-Ann; Lim, Kian-Ping (Taylor & Francis Group, 2009)
The finding of nonlinear cointegration between Asian exchange rates with the corresponding relative prices and aggregate price levels based on Breitung’s (2001) nonparametric rank tests reinforces previous validations of purchasing power parity (PPP) by the parametric testing procedures. Hence, the long-run Asian exchange rates are in equilibrium with the relevant fundamentals as suggested by the PPP hypothesis.